European cooperation in higher education : shaping the future of Europe - Kushnir, Iryna (Emerald Publishing Limited, 2025)
The ebook edition of this title is and freely available to read online. The European Higher Education Area (EHEA) is an international initiative for the harmonisation of higher education systems in its forty-seven active members. While literature about the participation of the UK, Germany, France and Italy in the EHEA is diverse, limited research explores them jointly as the four founding members of the EHEA. Revisiting the important foundation of the Bologna Process and the wider Europeanisation agendas associated with the creation of the EHEA, Iryna Kushnir examines the perspectives from these four key higher education stakeholders of the EHEA through the lens of rationale-choice neoinstitutionalist view of Europeanisation. This allows for the theorisation of Europeanisation within the context of the EHEA, an angle which is sometimes neglected or insufficiently addressed in literature. Focusing on their interconnectedness of their EHEA membership agendas and their wider political agendas, the four case studies concentrate on the significance of their membership in the EHEA post-2020, after the Brexit transitional period and the start of a full-scale war in Ukraine. This not only deepen our understandings of Europeanisation but forces us to reflect on the broader meaning of the term and, crucially, informs EHEA international level policy-making in the run-up to EHEA's new deadline of 2030.
Keywords: European Higher Education Area.; Education, Higher -- Europe.; Education -- Schools -- Levels -- Higher.; Higher education, tertiary education.; elektronické knihy; electronic books